Risk of thyroid cancer after therapeutic irradiation in adult patients: An Age‐Based surveillance, epidemiology, and end results analysis. (20th November 2019) - Dalwadi, Shraddha M.; Dorman, Clark; Fisher, Sarah B.; Bonnen, Mark; Grubbs, Elizabeth; Ludwig, Michelle S.
Abstract : Objectives/Hypothesis: One risk of radiation therapy exposure (XRTe) is second primary thyroid cancer (SPTC). Previous reports examined this in children, but no population‐based studies have explored XRTe and SPTC across all ages or stratified by histological subtypes. Study Design: Database study. Methods: We report patient characteristics of a Surveillance, Epidemiology, and End Results (SEER) dataset of SPTC (n = 4, 669) using χ 2 and t tests. Odds ratio (OR) for SPTC was determined based on age, histology, and XRTe compared to expected values in the SEER database. Kaplan‐Meier survival and Cox proportional hazard ratios were reported to determine factors influencing latent survival (LS; time from initial diagnosis to SPTC) and overall survival in univariate and multivariate models. Results: Extrathyroid extension and node status based on XRTe were similar ( P = .684 and P = .776, respectively). XRTe patients were more likely to have smaller tumors (17.6 vs. 19.3 mm, P = .007). XRTe patients were diagnosed with SPTC at younger ages (59.8 vs. 62.7 years, P  < .001) without a difference in LS (7.45 vs. 7.50 years, P = .426). Patients aged 1 to 14 years and 15 to 29 years at diagnosis of first cancer are at higher risk of SPTC after XRTe (OR = 1.89, P = .005 and OR = 2.35, P = .001, respectively), unlike patients age 30 to 44 years and 45+ years (OR = 1.03, P = .823 and OR = 0.97, P = .624, respectively). This difference is not present for follicular and medullary SPTC. Conclusions: Patients aged 30+ years receiving radiation therapy (XRT) do not have an increased risk of SPTC. Deliberation is necessary in recommending, planning, and delivering XRT to minimize risk of subsequent malignancy in younger patients. Level of Evidence: NA Laryngoscope, 130: 2081–2086, 2020